An Adult Loa loa Worm in the Upper Eyelid: An Atypical Presentation of Loiasis in the United States. (19th April 2021) - Rodriguez, Linnet; White, Julia Michelle; Richards, Nikisha Q.; You, Alan X.; Couser, Natario L.
Abstract : Purpose . To report a case of ocular involvement of Loa loa parasite. Observations . We present a rare case report of a Loiasis diagnosed in the United States from a patient presenting with subcutaneous migration of an adult worm within an eyelid who was found to have systemic disease with microfilaria in his blood. This is the second report in the United States and the eighth case in published literature worldwide. Conclusions and Importance . Due to the relatively mild disease course, Loiasis is relatively ignored in public health in low resource health districts. Understandably, the focus of public health in endemic areas must focus on basic health needs like malnutrition and diseases that entail a greater disease burden. As globalization has increased the amount of trade of physical goods, the effect of immigration also has implications for the spread of infectious disease. Medical practitioners in the United States should be aware of endemic diseases from foreign lands.